One Pot Multi Component Reaction (MCR) Catalysed by Montmorillonite K10 Under Microwave Conditions: Synthesis of Novel 1-(2,7-dimethyl-5- phenyl-5H-thiazolo[3,2-a]pyrimidin-6-yl)ethanone Derivatives - V.R. Sharma, G.; Devi, B.; Appala Naidu, A.; R. Robert, Alice (Current Microwave Chemistry, 2016)
Background: Organic reactions accelerated by microwave irradiation is an area of great interest in recent times. Several organic reactions are usually slow under normal or thermal conditions, however, use of microwave irradiation reduces the reaction time significantly. Multi component reactions (MCRs) are of interest due to nature of complex products formed in a one pot reaction. Methods: The reaction (MCR) is accelerated by montmorillonite K10 catalyst under microwave conditions. Results: Microwave assisted ‘montmorillonite K10’ catalysed synthesis of novel 1-(2,7-dimethyl-5-phenyl-5H-thiazolo[3,2-a]pyrimidin-6-yl)ethanone based fused heterocyclic compounds of medicinal interest is reported in this communication. The reaction is carried out by taking an aldehyde, amine and a 1,3 ketone (1:1:1), alongwith montmorillonite K10 (catalytic) in solvent free condition in an ecofriendly manner under microwave irradiation for about 5 mins followed by chromatography. All new compounds obtained in excellent yields are well characterized by 1HNMR, IR, Mass etc. Conclusion: A very efficient, MCR involving montmorillonite K10 catalyst and microwave irradiation is reported in this communication for the synthesis of several novel 1-(2,7-dimethyl-5-phenyl-5H-thiazolo[3,2-a]pyrimidin-6-yl)ethanone derivatives of medicinal interest.
Keywords: montmorillonite K10 catalyst